Technological Pedagogical Content Knowledge (TPACK) Framework for Science Teachers’ Comptences in Facing Global Challenges and Issues: A Narrative Literature Review - Abdul Latip; Babang Robandi; Amaliah Amaliah; Rifqi Rohmanul Khakim; Nurul Fatonah (International Journal of Pedagogy and Teacher Education, 2023)
Technological developments have made technology-assisted learning an essential part of educational areas. However, integrating technology in education requires teachers’ competency, called technological pedagogical content knowledge (TPACK). This study reviews the current body literature of TPACK regarding teachers’ challenges and demands of learning with global issues, such as the Industrial Revolution 4.0 and the SDGs 2030 agenda. Researchers employed Narrative Literature Review (NLR), where we reviewed TPACK, teacher competence, and challenges to global issues in education studies from various published articles. This study found a total of 27 articles published in the last ten years. In this study, NLR was carried out in 4 main stages: determining the topic, finding sources and references, analyzing relevant sources, and synthesizing the findings into a structured and informative narrative. The NLR results show that: 1) the form and type of technology integration in education needs to pay attention to aspects of pedagogy and content knowledge so the determination and use of technology in education can work effectively according to the characteristics of students and the content being taught; 2) forms and types of technology integration have been used include virtual labs, molecular and particle animation media, smartphone applications, and augmented reality; and 3) technology integration in the learning process indicated initial, core, and closing activities requiring various approach. Utilizing technology in education within the initial, core, and closing activities requires considering type and form of technology used according to pedagogical aspects (setting learning objectives) and content aspects (depth and breadth of material at each stage). The study results highlighted teachers' competencies on TPACK to effectively support teaching and learning processes in alignment with global needs and challenges.